Greece and the Augustan cultural revolution - Spawforth, Antony (Greek culture in the Roman world, 2012)
"This book examines the impact of the Roman cultural revolution under Augustus on the Roman province of Greece. It argues that the transformation of Roman Greece into a classicizing 'museum' was a specific response of the provincial Greek elites to the cultural politics of the Roman imperial monarchy. Against a background of Roman debates about Greek culture and Roman decadence, Augustus promoted the ideal of a Roman debt to a 'classical' Greece rooted in Europe and morally opposed to a stereotyped Asia. In Greece the regime signalled its admiration for Athens, Sparta, Olympia and Plataea as symbols of these past Greek glories. Cued by the Augustan monarchy, provincial-Greek notables expressed their Roman orientation by competitive cultural work (revival of ritual; restoration of buildings) aimed at further emphasising Greece's 'classical' legacy. Reprised by Hadrian, the Augustan construction of 'classical' Greece helped to promote the archaism typifying Greek culture under the principate"--